Mobile banking adoption in peripheral countries : the case of Portugal - Souto, Ana Sofia Santos (2020)
The present study originates from the theme of innovation, more specifically the innovation of the business model. Over the past few years, business models have gained increasing importance in business and academia because of their extreme importance to the success of any company or entity. In the financial and banking industry, technology has been evolving without any precedents, so banks seek to develop and innovate their business models in order to contribute positively to consumer expectations. Mobile bankig is a successful example. However, a question arises on the demand side, is the consumer ready to adopt such innovation from the banks? This investigation seeks therefore to understand the factors that may explain the adoption of mobile banking as being a bank innovation. To verify the importance of the dimensions of the model, a quantitative exploratory study was carried out through the application of a questionnaire given to adult individuals with a bank account in Portugal. A research model was created resulting from the combination of the variables identified in the Diffusion of Innovation theory, with the variables of perceived risk and personal innovativeness. The results show that the adoption of mobile banking is supported by relative advantage, compatibility, perceived risk and, finally, personal innovativeness.